Comparison between magnetic resonance spectroscopy and diffusion weighted imaging in the evaluation of gliomas response after treatment. Issue 12 (December 2015) - Lotumolo, Antonella; Caivano, Rocchina; Rabasco, Paola; Iannelli, Giancarlo; Villonio, Antonio; Antuono, Felice D'; Gioioso, Matilde; Zandolino, Alexis; Macarini, Luca; Guglielmi, Giuseppe; Cammarota, Aldo
Highlights: We compared magnetic resonance spectroscopy (MRS) and diffusion weighted imaging (DWI) in the assessment of brain tumors. In the case of HGG, the technique that better evaluates the response to treatment appears to be the MRS. In the case of LGG, the technique that better evaluates the response to treatment appears to be the DWI. Combination of DWI and MRS can help to characterize different changes related to treatment and to evaluate brain tumor response to treatment. Abstract: Purpose: To compare magnetic resonance spectroscopy (MRS) and diffusion weighted imaging (DWI) in the assessment of progression and regression of brain tumors in order to assess whether there is correlation between MRS and DWI in the monitoring of patients with primary tumors after therapy. Methods: Magnetic resonance imaging (MRI) has been performed in 80 patients, 48 affected by high grade gliomas (HGG) and 32 affected by low grade gliomas (LGG). The variation of apparent diffusion coefficient (ADC) value and metabolite ratios before and after treatment has been used to test DWI sequences and MRS as predictor to response to therapy. Comparison between post contrast-enhancement sequences, MRS and DWI has been done in terms of accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Moreover statistical correlation of ADC deviations with MRS metabolites variations before and after therapy have been studied. Results: In the case of HGG, MRS shows better sensitivity, specificity, PPV, NPV and accuracy compared to DWI, especially when considering the Choline/N-acetylaspartate (Cho/NAA) ratio. Regarding the LGG, the technique that better evaluates the response to treatment appears to be the DWI. A moderate correlation between ADC deviations and Cho, Lipide (Lip) and Lactate (Lac) has been found in LGG; while NAA revealed to be weakly correlated to ADC variation. Considering HGG, a weak correlation has been found between ADC deviations and MRS metabolites. Conclusion: Combination of DWI and MRS can help to characterize different changes related to treatment and to evaluate brain tumor response to treatment.